EFEKTIVITAS KEBIJAKAN PENGELOLAAN PASAR TRADISIONAL DI KABUPATEN OGAN KOMERING ULU - Yadi Lustiadi (Universitas Bandar Lampung (UBL), 2019)
The existence of the traditional market in public life would have can notdoubt.The price of a friendly, warm atmosphere, as well as the availability of a wide range of community needs making market forces pull all circles to do the buying and selling activities.Not without problems, the existence of the market are also sometimes also becomes its own problems for the Government and the community.Market conditions are far from treatment by the provider of the market makes the attractiveness of the market in the community be reduced.Not to mention when compared to modern market existence currently.There are some indicators that can then be used as a benchmark of the success of the management of traditional markets.Among them; aksessabilitas, convenience, and sufficiency. This research do using data collection through interviews, observation and documentation, in hopes of digging up the entire information about the management of traditional markets in the Regency of OganKomering Ulu, in accordance with the applicable local There are.The study was conducted at two nii traditional market in kabupatenOganKomering big Ulu, namely Tops markets and new markets.Based on the results of research, the aksesabilitas on the two traditional markets in the Regency of OganKomering Ulu has not done well, less slick pasasrpentaan makes the society's difficulty in accessing basic necessities.The level of comfort that dirasaskan by the stakeholders of both traditional market also has yet to be felt, the market conditions are cramped, the floors slippery and markets tend to be dirty, a pile of sambahdisudut-sudut market is the cause.In addition, talking about the adequacy of the market, as seen from the availability of buildings for merchants, market conditions are still far from enough, said the large number of traders still looks that don't get the kiosk was evidence yet to achieve this requirement.Therefore, it can be concluded that the management of traditional markets in the Regency of OganKomering Ulu has not yet reached the overall effectiveness.There needs to be the seriousness of the local government and the whole society to be able to achieve the goals of the management of traditional markets.